Understanding Youth Online Experiences and Mental Health: Development and Validation of the Digital Activity and Feelings Inventory (DAFI) - Katarzyna Kostyrka‐Allchorne; Jake Bourgaize; Aja Murray; Mariya Stoilova; Iqra Abbas; Amy Bridgwood; Eliz Azeri; Chris Hollis; Ellen Townsend; Sonia Livingstone; Edmund J. S. Sonuga‐Barke; the Digital Youth Research Programme (International Journal of Methods in Psychiatric Research)
ABSTRACT Objectives We created the Digital Activity and Feelings Inventory (DAFI) to measure youth digital activities and the psychological reactions they evoke, established its psychometric properties and tested its validity in predicting mental health relative to screen time estimates. Methods An initial pool of items was generated using the existing research on youth digital activity and mental health and further refined via consultations with experts and young people (online youth panel sessions, n = 14). The participants (n = 383, mean age = 19 years) completed the resulting DAFI alongside established measures of depression, anxiety, wellbeing, and screen time. The DAFI factor structure, reliability and predictive validity were tested. Results Exploratory factor analyses identified five digital activity subscales: Risky Content, Risky Interactions, Social Comparison, Leisure Activities and Social Engagement and three psychological reactions subscales: Negative Self‐Reactions, Negative Stress Reactions, and Positive Reactions. Internal consistency and test‐retest reliability were high. Social Comparison and Negative Self‐Reactions, but not screen time, independently predicted depression and anxiety symptoms. Positive Reactions, lack of Negative Self‐Reactions, lower screen time and Social Engagement predicted wellbeing. Conclusion The DAFI is a reliable measure of digital activities and associated psychological reactions and predicts youth mental health better than screen time.